Examining the Challenges and Benefits of Work from Home for IT Professionals (Cuestiones de Fisioterapia, 2024)
This study examines the challenges and benefits of the work-from-home (WFH) model for Information Technology (IT) professionals, a sector significantly impacted by the widespread adoption of remote work policies, particularly following the COVID-19 pandemic. Employing a descriptive and exploratory survey design with a quantitative approach, the study collected data from 467 IT professionals across various cities in Uttar Pradesh, India, using a structured Likert-scale questionnaire. The findings revealed that the most prominent challenges constitute "Psychosocial and Operational Challenges of Remote Work." including increased working hours, feelings of isolation, lack of immediate support, technological difficulties, communication gaps, and impacts on professional growth. Conversely, the key benefits are encapsulated in "Positive Work-Life Balance and Empowerment through Remote Work," such as enhanced job satisfaction, better work-life balance, autonomy, and self-discipline. Notably, chi-square analysis indicated no statistically significant associations between demographic variables (gender, age, marital status, designation, tenure) and the perceived levels of both challenges and benefits. The study concludes that while remote work presents universal challenges related to well-being and logistics, it also offers widespread benefits regarding flexibility and empowerment across diverse employee groups. The practical implications highlight the need for IT organizations to recognize remote work as a comprehensive psychosocial environment, necessitating investments in digital infrastructure and proactive employee support systems. Standardized policies addressing workload, communication, and well-being can benefit all employees, fostering a resilient and productive remote workforce. Keywords Work from Home (WFH), IT Professionals, Challenges of Remote Work, Benefits